Control method of applied voltage for fabricating micro-pattern using near-field electrohydrodynamic direct-writing technology - Ting Wu (AIP Publishing LLC, 2021)
In the process of fabricating micro-patterns using the near-field electrohydrodynamic (EHD) direct-writing technology, the voltage error and the dynamic responsiveness of applied voltage have an effect on the jetting shape and the direct-writing pattern. To solve these problems, an iterative control method was proposed to compensate the voltage error between the expected voltage and the actual voltage of the near-field EHD direct-writing setup, which was controlled by the idea of iteration, and a control method based on feedforward and feedback was proposed to enhance the dynamic response of applied voltage in the process of the near-field EHD direct-writing micro-pattern, which was controlled by the idea of the feedforward and feedback. Software algorithms of the voltage error compensation and improved dynamic response of applied voltage were implemented in the near-field EHD direct-writing setup. The experimental results show that the proposed method of voltage error compensation can effectively improve the precision of applied voltage and the presented control method of improving dynamic response capability can effectively shorten the delay time of applied voltage. Finally, two groups of contrast experiments were carried out in the near-field EHD direct-writing equipment, and the experimental results demonstrate that the proposed control methods can effectively improve the jetting shape and the quality of the direct-writing micro-pattern.